"Are They Mental Health or Behavioral?": Toward object relations translation for corrections officers. (14th March 2019) - Gangemi, Stephanie A.
Abstract: Correctional institutions, particularly correctional security staff (corrections officers, deputies, and other custodial staff) are increasingly relied upon for the management of some of the most severely disturbed and impaired members of society. Lack of mental health training for correctional staff poses problems that include safety risk, lack of empathy, inmate abuse, staff burnout, and trauma, as well as missed opportunities for rehabilitative efforts. This paper proposes that salient concepts from psychoanalysis, particularly object relations theory, can and should be integrated into training for correctional security staff. Using the acronym "PSYCHIATRIC, " relevant object relations concepts are translated into practical correctional language. Increasing accessibility to object relations theory offers opportunity for interdisciplinary collaboration and effective use of correctional staff members' time and expertise, while supporting the mental health of inmates and staff members. The case vignettes of Jack and Kayleen explore staff/inmate dynamics through an object relational lens. Further exploration, implementation, and evaluation of object relations informed training tools are suggested to evaluate impact and efficacy.